Anterior cruciate ligament (ACL) reconstruction and meniscal repair rates have both increased in the past 20 years in England: hospital statistics from 1997 to 2017 - Abram, SGF; Price, AJ; Judge, A; Beard, DJ (BMJ Publishing Group, 2019)
Objectives We investigated the temporal trend and the geographical variation in the rate of an anterior cruciate ligament (ACL) reconstruction and meniscal repair (MR) performed in England during a 20-year window.